Barriers and Facilitators for Smoking Cessation in Chinese Smokers with Chronic Obstructive Pulmonary Disease: A Qualitative Study - Zhang YY; Tang WT; Zhang H; Wang J; Bai XX; Liao YH; Robinson N; Liu JP (International Journal of COPD, 2022)
Ying-Ying Zhang,1 Wen-Tao Tang,2 Hong Zhang,3 Jing Wang,3 Xiao-Xu Bai,3 Yan-Hui Liao,4 Nicola Robinson,1,5 Jian-Ping Liu1 1Centre for Evidence-Based Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China; 2Pingyi Hospital of Traditional Chinese Medicine, Linyi, Shandong, People’s Republic of China; 3Fangshan Hospital of Traditional Chinese Medicine Affiliated to Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 4Department of Psychiatry, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310016, People’s Republic of China; 5Institute of Health and Social Care, London South Bank University, London, UKCorrespondence: Jian-Ping Liu, Centre for Evidence-Based Chinese Medicine, Beijing University of Chinese Medicine, 11 Bei San Huan Dong Lu, Chaoyang District, Beijing, 100029, People’s Republic of China, Email liujp@bucm.edu.cn; jianping_l@hotmail.comBackground: Smoking cessation is recommended as a key intervention for chronic obstructive pulmonary disease (COPD) smokers. However, in China, few COPD smokers quit successfully. The aim of this study was to explore in depth the barriers and facilitators for smoking cessation among smokers with COPD in China.Methods: A purposive sample of 32 hospitalized smokers with COPD were included, 17 ex-smokers and 15 current smokers, participated in the semi-structured interviews. Interviews were analyzed thematically and using a deductive approach guided by Capability, Opportunity, Motivation-Behavior (COM-B) framework.Results: Three inter-related themes were generated: smokers’ motivation was a prerequisite for quitting, maintaining capability to quit smoking, and opportunities that facilitated smokers to quit. Motivation to quit for most participants was activated by COPD-related symptoms, although they had a limited knowledge of COPD. Physical benefits from quitting and strong willpower were facilitators for maintaining quitting, while exposure to smoking environment and strong addiction to nicotine were frequent reasons for relapse. Most ex-smokers quit smoking by their own willpower rather than professionally delivered smoking cessation interventions. Smokers’ attitudes toward these interventions depended on their effectiveness and convenience. Very few participants had experienced pharmacotherapy or behavioral support from physicians. However, interviewees preferred auricular acupressure to pharmacotherapy.Conclusion: Motivation to quit among smokers with COPD was usually initiated by COPD-related symptoms. Physical benefits observed by quitting and strong willpower facilitated smoking cessation, while exposure to smoking environment and strong addiction to nicotine led to relapse. COPD smokers in China preferred auricular acupressure to pharmacotherapy.Keywords: chronic obstructive pulmonary disease, smoking cessation, tobacco, qualitative research, acupuncture